Levels of Squamous Cell Carcinoma Antigen and Interleukin-6 as Biomarkers in NSCLC Patients - Lydia Arieta; Noni Novisari Soeroso; Setia Putra Tarigan; Putri Chairani Eyanoer (Sumatera Medical Journal, 2025)
Background: Squamous Cell Carcinoma Antigen (SCC-Ag) and Interleukin-6 (IL‐6) has been widely used for monitoring Non-Small Cell Lung Cancer (NSCLC). Objective: This concentration also known to be higher in Non Small Cell Lung Cancer. Methods: This research used descriptive study among NSCLC patients. Blood sampling was used with serum. ELISA platform was used to rate SCC-Ag and IL-6 serum. Results: From 20 samples NSCLC, we found 20 males (100%), active smokers (80%). From histology type, Adenocarcinoma 12 cases (60%). The most of subjects were in stage IVA (70%). The Squamous Cell Carcinoma Antigen levels of NSCLC patients showed that as many as 20 samples (100%) were within normal limits and did not show an increased. Conclusion: Levels of IL-6 increased as many as 15 samples (75%), and IL-6 levels were still within the normal range sample (25%). Tumor marker are not meant to detect marker growth, but only as a marker that found in lung cancer,but IL-6 as the one of the pro-inflammation cytokines that shows an increased in patients NSCLC.